Decision Support Systems A Game Changer in the Field of Education - Lestari Wiwik; Siti Irene Astuti Dwiningrum; S Sujarwo (STAI Hubbulwathan Duri, 2023)
This study employed the Simple Additive Weighting (SAW) method within a Decision Support System (DSS) to evaluate student admissions in the field of education. By assigning weights to criteria and calculating weighted scores for alternatives, the study ranked the applicants and identified the most preferred choices. The results revealed that the ranking process considers multiple factors and their respective weights to determine the relative performance of each alternative. It assists decision-makers in selecting the solutions that most effectively align with their criteria and objectives. This facilitates informed decision-making. Educational institutions can streamline the admissions process by assessing the alternatives and scrutinizing each applicant's performance against many criteria. This approach enhances the equity, clarity, and impartiality of decision-making. The findings highlight the effectiveness of the SAW method and DSS in facilitating data-driven decision-making processes in education. However, limitations in subjective weight assignment and criteria selection should be considered. Future research should explore alternative decision analysis techniques and address implementation challenges.